Methods Of Teaching Of Aggression Theories - Ayvazyan, Anjelika (Զանգակ հրատ.)
The article presents a brief overview of the theoretical study of aggression and methods of teaching the fundamental theories of aggression. It is shown that the problem of studying the phenomenon of aggression in modern society is widely widespread. Different teaching methods are characterized, with the help of which an empirical study was conducted. The general purpose of the study is presenting the idea of the need to study teaching methods in the psychology of aggression. The study’s main result was that the process of teaching the theories of aggression is accompanied by a significant emotional load. Students tend to perceive the subject of learning through the prism of personal experience and emotional experiences. The article emphasizes the need for further research in order to develop an optimal teaching method. The scientific innovation of this study is a manifestation of the trends of aggression theories interpretations.
Keywords: Psychology